The art of adaption: the National Arts Festival's strategic response to the COVID-19 pandemic - Brody, Blake Benjamin (Rhodes University, Faculty of Commerce, Rhodes Business School)
The National Arts Festival (NAF), an annual event held in South Africa, faced a significant challenge in 2020 due to the COVID-19 pandemic. The traditional in-person format of the festival was no longer feasible due to government restrictions. In response, the NAF's CEO, Monica Newton, led her team in a rapid transition to a virtual platform. This decision-making process and the creation of the first virtual NAF (vNAF) occurred within a remarkably short period of 100 days. This teaching case study delves into the academic framework of crisis management, stakeholder theory, strategic thinking, strategic management, and business models, examining their application in the context of the NAF's transformation. To understand the decision-making process and challenges faced by the NAF, a qualitative research design was employed. Data collection involved two face-to-face interviews with Monica Newton, CEO of the NAF, and secondary sources. The teaching case is accompanied by a comprehensive note for educators, offering guidance on its classroom use. The note includes a case synopsis, intended audience, suggested learning outcomes, theoretical connections, teaching strategies, potential discussion questions, evaluation methods, and additional resources. It supports a multi-faceted analysis of the NAF's transformation and encourages vibrant class discussion.
Keywords: Standard Bank National Arts Festival; Strategic planning; Strategic thinking; Crisis management -- South Africa; Business model; Stakeholder management; COVID-19 Pandemic, 2020- Influence